Potential Combination of Bittern Water with Vitamin B Complex for Mineral Deficiency Therapy in Cattle: A Literature Study - Megawati, Ega; Sriwidodo, Sriwidodo; Setyabudi, Iwan (Universitas Airlangga, 2021)
Bittern water is a byproduct of the crystallization process from the manufacture of salt which have high concentrations of magnesium, calcium, potassium and other trace minerals Bittern water is known to treat osteoporosis, postprandial hyperlipidemia, oral infections and increase salivary secretion. The mineral content in bittern water is not only beneficial for humans but also for animal health. Cows are one of the animals that are prone to various health problems such as mineral balance and metabolism disorders in the body, especially during pregnancy and after giving birth. In addition to minerals, vitamin B complex is often used to improve the health quality of cows. However, until now, the use of bittern water and the combination with vitamin B complex for animal treatment is still very rare. The formulation of multivitamin-mineral preparations is quite complex to do so that there are several things that need to be considered in order to obtain a good and quality formula. This review article was created to gather information regarding the benefits of the mineral content contained in bittern water and vitamin B complex as a treatment to treat various health problems for cattle, as well as what important factors should be considered in multivitamin-mineral preparations. Based on literature search, it was found that the combination of bittern water and vitamin B complex has the potential to overcome health problems in cows, where the main minerals in bittern water are proven to improve magnesium status in the blood, increase calcium intake and reduce the incidence of milk fever, increase milk production and components, and improve immune status. While vitamin B complex is widely used as a supplement to increase metabolism, energy status in cows balances rumen pH, maintains microbiota balance in riumen and helps increase milk production. The combination of bittern water and vitamin B complex can synergistically improve mineral status, energy, and immune response, as well as improve disease symptoms. There are also important factors that must be considered in multivitamin-mineral dosage formulations for animals, namely bioavailability, stability, and dosage form.